2D Maps for Visual Analysis and Retrieval in Large Multi-Feature 3D Model Databases - Bustos, Benjamin; Keim, Daniel A.; Panse, Christian; Schreck, Tobias (2004 IEEE Visualization Conference, 2004)
Multimedia objects are often described by high-dimensional feature vectors which can be used for retrieval and clustering tasks. We have built an interactive retrieval system for 3D model databases that implements a variety of different feature transforms. Recently, we have enhanced the functionality of our system by integrating a SOM-based visualization module. In this poster demo, we show how 2D maps can be used to improve the effectiveness of retrieval, clustering, and over-viewing tasks in a 3D multimedia system.